The boxcar librarian ebook A novel. - Labuskes, Brianna (2025)
Inspired by true events, a thrilling Depression-era novel from the author of The Librarian of Burned Books about a woman's quest to uncover a mystery surrounding a local librarian and the Boxcar Library—a converted mining train that brought books to isolated rural towns in Montana. When Works Progress Administration (WPA) editor Millie Lang finds herself on the wrong end of a potential political scandal, she's shipped off to Montana to work on the state's American Guide Series—travel books intended to put the nation's destitute writers to work. Millie arrives to an eclectic staff claiming their missed deadlines are due to sabotage, possibly from the state's powerful Copper Kings who don't want their long and bloody history with union organizers aired for the rest of the country to read. But Millie begins to suspect that the answer might instead lie with the town's mysterious librarian, Alice Monroe. More than a decade earlier, Alice Monroe created the Boxcar Library in order to deliver books to isolated mining towns where men longed for entertainment and connection. Alice thought she found the perfect librarian to staff the train car in Colette Durand, a miner's daughter with a shotgun and too many secrets behind her eyes. Now, no one in Missoula will tell Millie why both Alice and Colette went out on the inaugural journey of the Boxcar Library, but only Alice returned. The three women's stories dramatically converge in the search to uncover what someone is so desperately trying to hide: what happened to Colette Durand. Inspired by the fascinating, true history of Missoula's Boxcar Library, the novel blends the story of the strong, courageous women who survived and thrived in the rough and rowdy West with that of the power of standing together to fight for workers' lives. And through it all shines the capacity of books to provide connection and light to those who need it most.